(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Workplace bullying has a negative impact on the efficiency of the working force and combined productivity of any organization. As per the literature available on “Workplace bullying” the concept is widely discussed and acknowledged in different aspects globally. With the available literature, it is still the need of hour to find the gaps in the literature to cope with bullying taking place in an organization. The aim of this study is to explore the concept of workplace bullying in available literature and share a combined review with possible areas for research in future. This study offers the structured review on a total of 40 research articles. By the end of the review, this paper will be able to answer all the queries regarding the concepts of bullying. This review will provide awareness about Workplace bullying, discuss solutions, and bring attention to the laws regarding Workplace bullying and suggest future implications.